MO326CORTICOSTEROIDS FOR THE TREATMENT OF AUTOIMMUNE DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS OF REPORTED ADVERSE EVENTS IN RANDOMISED CONTROLLED TRIALS. (29th May 2021) - Major, Rupert; Grant, Robert; Nockels, Keith; Das, Mrinal; Floege, Jürgen; Barratt, Jonathan
Abstract: Background and Aims: Systemic corticosteroids are commonly used to treat autoimmune diseases such as immunoglobulin A (IgA) nephropathy. Corticosteroids are associated with increased risk of adverse events such as weight gain, hyperglycaemia, hypertension, infection and bone fracture occur frequently and affect safe long-term use. Adverse events of corticosteroids in clinical trials may have been historically under-reported. We aimed to perform a systematic review and meta-analysis of reported adverse events of corticosteroids in autoimmune diseases, with a particular focus on kidney pathologies. Method: Pre-registered protocol systematic review (Prospero ID: CRD42020206650). The following databases were searched from 1980 to 2020: OVID MEDLINE Cochrane Library database of controlled trials (CENTRAL), to include: NIH Clinical Trials Database (ClinicalTrials.gov) WHO International Clinical Trials Registry Platform (who.int/ictrp/en) EU Clinical Trials Registry (clinicaltrialsregister.eu) Placebo-controlled trials in adults with any form of autoimmune disease receiving intravenous or oral corticosteroids were included in the systematic review. Trial protocol major adverse events and all-cause mortality were included as the current study's main outcome. Results: After exclusion of duplicates between databases, 4490 OVID MEDLINE and 4987 Cochrane abstracts were reviewed. In total, 110 published clinical trials were identified for inclusion in the study: 14 clinical trials were in kidney autoimmune diseases, including 8 in IgA nephropathy. Results of their published adverse events, including where appropriate meta-analysis, will be presented. Specific results of those studies of kidney pathologies such as IgA nephropathy will be presented. Conclusion: This systematic review with a pre-registered protocol identified 110 clinical trials examining systemic corticosteroid use versus placebo in autoimmune diseases. These results will help to understand whether the risks of systemic corticosteroids for autoimmune disease has been historically under-reported in the medical literature and whether a clear risk and benefit profile of corticosteroids in autoimmune disease can be assessed.